Pelestarian Budaya Suku Sawang di Kabupaten Belitung Timur - Sahya Anggara (LP2M ISBI Bandung, 2018)
ABSTRACTSawang culture preservation in East Belitung regency faces many obstacles. Less role of local government, lack of regeneration, and the infiltration of other cultures, causing Sawang culture continue to erode and it is going to extinction. The preservation of Sawang culture, in Selinsing Village, Gantung District, East Belitung Regency needs to be improved further through appropriate programs from Culture and Tourism Department of East Belitung Regency, so that the culture keeps growing among Sawang community. Through qualitative and descriptive analysis with sociology, anthropology, and public policy approaches, this research aims to find methods to preserve and to develop Sawang culture so it can provide input for the local government to preserve Sawang culture.Keywords: policy, culture, Sawang ethnic, preservation ABSTRAK Pelestarian budaya Suku Sawang di Kabupaten Belitung Timur banyak mengalami hambatan. Kurang optimalnya peran pemerintah daerah, kurangnya regenerasi budaya dan pengaruh budaya luar, menyebabkan budaya Suku Sawang terus tergerus dan terancam mengalami kepunahan. Pelestarian budaya Suku Sawang, di Desa Selinsing, Kecamatan Gantung, Kabupaten Belitung Timur perlu lebih ditingkatkan melalui program pembinaan yang baik dari Dinas Kebudayaan dan Parwisata Kabupaten Belitung Timur, sehingga budaya tersebut tetap tumbuh dan terus berkembang di kalangan masyarakat Suku Sawang. Melalui penelitian deskriptif kualitatif dengan pendekatan sosiologi, antropologi, dan kebijakan public, diharapkan penelitian dapat menjadi bahan masukan bagi pemerintah daerah dalam rangka pelestarian dan pengembangan budaya Suku Sawang agar tidak mengalami kepunahan.Kata kunci: kebijakan, budaya, Suku Sawang, pelestarian